Penilaian Kinerja di Perusahaan Daerah Air Minum (PDAM) Kabupaten Pasuruan dari Perspektif Finansial dan Non Finansial - Manafe, Prilia Herdiyani (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
This research aims to know the performance of PDAM through financial and non financial perspektive. This research employs descriptive qualitative approuch. The data are collected by observation, interview, questionnaires and documentation. The data analysis is conducted by measuring each perspective, the financial and non-financial perspective, which consists of customers, internal business, learning and growth. The result of the research shows that, overall, the performance of PDAM in Pasuruan Regency is good. It is indicated by the high value acqusition from each perspective. Based on the financial perspective to measure the profitability ratio, the ratio indicating the highest increase is ROI, compared to other ratios namely ROE, operating expenses ratio, and NPM. The customer’s perspective which is measured using questionnaires shows the index value of the highest customer’s satisfaction criteria. In addition, as seen from customer’s acqusition and retention, the company is able to retain its customers, but there is an increase in customer complaint number. Based on the company internal business perspective, the company has given good services for the customers. The learning and growth perspective show a good performance, overall